Attachment patterns moderate the relation between coping flexibility and illness acceptance among kidney transplant recipients. Issue 5 (3rd September 2018) - Hamama-Raz, Yaira; Bergman, Yoav S.; Ben-Ezra, Menachem; Tirosh, Yael; Baruch, Roni; Nakache, Richard
ABSTRACT: Background and Objectives: Post-transplant kidney recipients may experience psychological concerns which have been associated with negative health behaviors. Illness acceptance might have an important role in this process. In line with the Conservation of Resources Theory (COR), the current study aimed to examine the relationship between coping flexibility, attachment patterns and illness acceptance among post-transplant kidney recipients, and to evaluate whether attachment patterns moderate the link between coping flexibility and illness acceptance. Design: The study employed a cross-sectional design. Methods: Ninety-four post-transplant kidney recipients completed questionnaires assessing demographic and medical characteristics, illness acceptance, coping flexibility and attachment patterns. Results: Our results indicated that coping flexibility was positively associated with illness acceptance. Moreover, attachment moderated this link, as high coping flexibility was associated with increased illness acceptance among individuals with low levels of attachment anxiety, a finding which was not significant when high levels of anxiety were reported. Conclusions: This study highlights the potential importance of building greater flexibility in order to enhance illness acceptance among kidney transplants recipients. Moreover, the role of insecure attachment patterns in health-related outcomes among kidney transplants recipients is emphasized.